(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s economic landscape relies heavily on its agricultural sector, which constitutes 14.4% of the Gross Value Added (GVA) as of 2018-19. The Dairy Sector emerges as a significant driver, holding the distinction of being the largest contributor to the agricultural GDP. Rajasthan, with its substantial processing of agricultural goods, stands as the linchpin of the state’s economy. Moreover, it claims the title of the second-largest milk-producing state in India, contributing approximately 11% to the national milk production within the agricultural sector. A pivotal player in this scenario is SARAS, the exclusive cooperative society in Rajasthan, playing a vital role in bolstering the state’s economy. The state government’s role becomes paramount in sustaining and amplifying this contribution through effective policies, regulations, and support mechanisms encompassing infrastructure, financial aid, and subsidies. Recognizing this, both central and state governments continually introduce diverse schemes and policies aimed at nurturing the growth of the dairy industry. According to ongoing research, optimizing and expanding the state government’s support system could exert a profound influence on India’s GDP growth, ultimately benefiting all states in the country. In broader terms, the dairy and animal husbandry department collectively makes a substantial contribution, amounting to 4.5% of the total Gross Domestic Product. Notably, the dairy industry alone constitutes a quarter of the entire agricultural output in India. These figures underscore the economic significance of the sector and emphasize the potential for further growth and development through strategic government support and interventions.